Impact of intergenerational support on older adults’ care expectations in rural areas in China - Wu, Lianxia; Xie, Tong; Guan, Weihua; Li, Wei (Frontiers in Public Health, 2024)
IntroductionAs rural-to-urban migration accelerates, rural areas are experiencing a significant increase in empty-nesters among the older adults. Influenced by traditional concepts of filial piety, older adults in rural areas heavily rely on the family-based old care model, creating a complex interplay between supply and demand for older adults’ care. This study investigates the relationship between intergenerational support and older adults’ care expectations in rural areas. We construct measures of financial and care expectations of older adults’ care to reflect older adults’ intentions and choices.MethodsThis study uses data from the 2018 China Health and Retirement Longitudinal Study and rural case studies to employ a binomial logit regression model, moderation effect analysis, and in-depth interviews.ResultsOur research reveals that the level of financial expectations for older adults’ care is inversely related to the extent of financial support from the parental generation but positively related to the level of financial support from the offspring. However, the older adults’ care expectations do not appear to be influenced by intergenerational support. Furthermore, population characteristics of the parental generation, such as educational attainment, age, and marital status, moderate the relationship between intergenerational support and older adults’ care expectations. Educational attainment negatively moderates the impact of parental financial support on financial expectations, age positively moderates offspring’s financial support on financial expectations. However, age negatively moderates offspring’s financial support on care expectations, while marital status positively moderates offspring’s financial support on care expectations.DiscussionThese findings help to elucidate the older adults’ care expectations of rural residents during the process of urbanization and social transformation, offering family-centered solutions such as ‘promoting cohabitation or proximity of children to their parents, developing diverse older adults’ care models based on different family situations, and ensuring the provision of basic older adults’ care services’ to address the current challenges of rural older adults’ care in China.